'For Time is / nothing if not amenable' — exemplarity, time, reception. (3rd January 2020) - Güthenke, Constanze
Abstract: This article revisits exemplarity as a strategy of approaching, reading, and using the past. By going beyond treating it mostly as a historical phenomenon, in terms of its use as a purely pre-modern rhetorical trope connected to historical and ethical writings in the Greek and Roman world, I suggest that exemplarity has critical potential to make us reconsider its ability to break through temporalities in a calculated and sceptical way. As such, it offers a provocation to Reception Studies to engage with exemplarity both in and as a more deliberate and strategic manner.